Knowledge About the Prevention of Covid-19 in the Community of Soropia District, Konawe Regency, Southeast Sulawesi Province, Indonesia - Rezky Yulinasari Ilham; Pitrah Asfian; Marsella Marsella; Gamser Gamser; Nurfila Taufik; Satria Lestari K Lestari K; Wa Ode Rahmadani Anoamo (Journal of Health Science and Pharmacy, 2024)
Background: The Covid-19 pandemic has become one of modern history's most significant global health events. Its rapid spread and far-reaching impact have forced people to adopt strict preventive measures to protect themselves and others. Knowledge of Covid-19 prevention is essential to reduce the risk of transmitting the virus and limit the pandemic's impact. This paper will discuss the importance of learning about Covid-19 prevention in the community. Objectives: To analysis knowledge about the Prevention of Covid-19 in the Community of Soropia District, Konawe Regency, Southeast Sulawesi Province, Indonesia Methods: The type of research used is descriptive research. Respondents were given a questionnaire in the form of a Google form via WhatsApp social media. The sample is the Community of Soropia District, Konawe Regency, Southeast Sulawesi Province. The sampling technique used is the Simple Random Sampling technique. Results: in the statement Covid-19 is a disease that is not dangerous and is the same as the common cold, 17.7% of respondents chose true, 67.9% chose false, and 14.4% did not know. On other questions, such as "Coronavirus can survive several hours outside the human body," 56.6% of respondents chose true, 21.5% chose incorrectly, and 21.9% did not know. Conclusion: The coastal communities of Soropia District, Konawe Regency, have a good level of knowledge because they understand fundamental things about Covid-19, although some people still don't understand. Keywords: knowledge; Covid-19; Indonesia